2016
DOI: 10.1371/journal.pone.0157870
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Contribution of Biofilm to the Pathogenesis of Peritoneal Dialysis Infections: Characterization and Microbial Behaviour on Dialysis Fluids

Abstract: Infections are major complications in peritoneal dialysis (PD) with a multifactorial etiology that comprises patient, microbial and dialytic factors. This study aimed at investigating the contribution of microbial biofilms on PD catheters to recalcitrant infections and their interplay with PD related-factors. A prospective observational study was performed on 47 patients attending Centro Hospitalar of Porto and Vila Nova de Gaia/Espinho to whom the catheter was removed due to infectious (n = 16) and non-infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…[1,55], were not significantly altered or increased in ESKD PD patients in comparison to ESKD non-PD patients. The existence of biofilms on PD catheters could explain the increase in Pseudomonaceae in the peritoneal microbiomes of ESKD PD patients [56,57]. However, this explanation is probably incorrect, as no new OTUs of Pseudomonas were generally found in ESKD PD patients; the variation observed in PD patients is an increase in OTUs also present in non-PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1,55], were not significantly altered or increased in ESKD PD patients in comparison to ESKD non-PD patients. The existence of biofilms on PD catheters could explain the increase in Pseudomonaceae in the peritoneal microbiomes of ESKD PD patients [56,57]. However, this explanation is probably incorrect, as no new OTUs of Pseudomonas were generally found in ESKD PD patients; the variation observed in PD patients is an increase in OTUs also present in non-PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…These infections are associated with lower cure rates, more catheter removals, and more frequent transfers to HD compared with other peritonitis episodes (9,10). Relapsing peritonitis is often linked to the colonization of the catheter with the presence of a biofilm in its intra-abdominal portion that should lead to catheter replacement (11,12).…”
mentioning
confidence: 99%
“…The reason of recurrence may be biofilm formation on the surfaces of catheter. Recently, Joana et al [23] found that no major differences on microbial density of the catheter cultures were observed between the catheters removed due to infectious and non-infectious causes. However, microbial yields were higher on the cuffs of catheters removed due to infection, which indicated that microbial biofilm is universal in PD catheters with the subclinical menace.…”
Section: Discussionmentioning
confidence: 99%